The Relationship Between Age and Room Temperature with Work Stress in Administrative Employees of PG. Purwodadi Magetan - Ningtias, Alfiyah Wahyu; Wibowo, Pipid Ari; Marsanti, Avicena Sakufa (Eduvest - Journal of Universal Studies, 2025)
Stress that occurs in the workplace is a feeling of pressure on employees that arises due to a lack of balance between individual abilities and the work environment. Employees face many challenges, such as the increasing amount of work and the need for knowledge that needs formal training, the high level of productivity and creativity expected. The purpose of this study was to analyze the relationship between age and physical environment with work stress in PG Administration employees. Purwodadi. This type of research is quantitative research with a cross sectional approach method. Data analysis using univariate analysis and bivariate analysis using Chi square test statistics. The population amounted to 47 administrative employees and a sample of 43 employees using proportional random sampling. The results of the bivariate test showed that there was a significant relationship between the independent variables, namely age (p-value = 0.008) and there was no significant relationship between the independent variables of room temperature (p-value = 0.760). The conclusion is that the room temperature variable has no relationship with work stress, while age has a relationship with work stress. Suggestions for PG. Purwodadi is to pay more attention to the burden and tasks given to employees specifically.